Effects of pessimism, depression, fatigue, and pain on functional health-related quality of life in patients with resected non-advanced breast cancer. (April 2019) - Calderon, Caterina; Carmona-Bayonas, Alberto; Hernández, Raquel; Ghanem, Ismael; Castelo, Beatriz; Martinez de Castro, Eva; Ferreira, Estrella; Ciria, Laura; Muñiz, María; Jimenez-Fonseca, Paula
Abstract: Introduction: The aim was to analyze the effects of pessimism, depression, fatigue, and pain on functional health-related quality of life (HRQoL) in patients with resected, non-advanced breast cancer. Methods: A prospective, multicenter study was conducted in 440 breast cancer patients. They completed the Brief Symptom Inventory (BSI), the European Organization for Research and Treatment of Cancer QoL-Questionnaire-Core-30 (EORTC-QLQ-C30), and the Revised Life Orientation Test (LOT-R). Results: Prevalence rates of pessimism and depression were 23.3% and 40.0%, respectively. Fatigue and pain were the most common symptoms, 8.8% and 4.2%, respectively. Patients without a partner were more pessimistic that partnered ones; those with a lower level of education and subjects without a partner exhibited more depression. Depression was a major factor that proved to have the greatest explanatory power for HRQoL (physical, role, emotional, cognitive, and social functioning) and global health status (R 2 range: 0.13 to 0.39). Of the five domains, fatigue had a significant effect on four and pain, on two. Conclusion: This study reveals the impact of depression and pessimism on physical, psychological, social, and quality-of-life aspects and the importance of evaluating them in patients who are going to initiate adjuvant chemotherapy for breast cancer. Highlights: Pessimism was related to marital status in women with breast cancer. Fatigue and pain are highly related factors. Fatigue, pain and depression predict self-reported health complaints in women with breast cancer.